'RA and the microbiome: do host genetic factors provide the link?. (May 2019) - Wells, Philippa M.; Williams, Frances M.K.; Matey-Hernandez, M.L.; Menni, Cristina; Steves, Claire J.
Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease, characterised by painful synovium inflammation, bony erosions, immune activation and the circulation of autoantibodies. Despite recent advances in therapeutics enabling disease suppression, there is a considerable demand for alternative therapeutic strategies as well as optimising those available at present. The relatively low concordance rate between monozygotic twins, 20–30% contrasts with heritability estimates of ∼65%, indicating a substantive role of other risk factors in RA pathogenesis. There is established evidence that RA has an infective component to its aetiology. More recently, differences in the commensal microbiota in RA compared to controls have been identified. Studies have shown that the gut, oral and lung microbiota is different in new onset treatment naïve, and established RA patients, compared to controls. Key taxonomic associations are an increase in abundance of Porphyromonas gingivalis and Prevotella copri in RA patients, compared to healthy controls. Host genetics may provide the link between disease and the microbiome. Genetic influence may be mediated by the host immune system; a differential response to RA associated taxa is suggested. The gut microbiome contains elements which are as much as 30% heritable. A better understanding of the influence of host genetics will shed light onto the role of the microbiome in RA. Here we review the role of the microbiome in RA through the lens of host genetics, and consider future research areas addressing microbiome study design and bioinformatics approaches. Graphical abstract: Putative interactions mediating the link between host genetic factors, the gut and oral microbiome and rheumatoid arthritis.Image 1 Highlights: Rheumatoid arthritis (RA) affects 1% of the population and is highly debilitating. RA is 65% heritable, yet the concordance rate between monozygotic twins is just 20–30%, indicating a substantive role of other risk factors. Studies have shown that the gut, oral and lung microbiome is different in treatment naïve and established RA patients, compared to controls. Current findings suggest an important influence of host genetics on the microbiome, which may contribute to RA via the host immune system. Associations of the microbiome with RA described thus far are confounded by host genetics, and future studies need to take account of this.